Comparison of Latanoprostene bunod 0.024% and Latanoprost 0.005% in Open-Angle Glaucoma or Ocular Hypertension. - Careaga Cacace, David Mateo; Arrúa Caballero, Martín Fernando; González Sanabria, Luis; Vera Duarte, Guillermo Raúl (Medicina Clínica y Social, 2023)
Introduction: Glaucoma is the main cause of irreversible blindness worldwide. The global prevalence of glaucoma in people aged 40 to 80 years is estimated at 3.5%. With the increasing number and proportion of older people in the population, it is projected that 111.8 million people will have glaucoma by 2040. First-line treatment is usually a topical IOP-lowering medication or laser trabeculoplasty. The most widely used class of medication is prostaglandin analogues. Objective: To compare the intraocular pressure (IOP) lowering effect of 0.024% Latanoprostene bunod (LBN) with 0.005% Latanoprost in subjects with open-angle glaucoma (OAG) or ocular hypertension (OHT). Methodology: Prospective, randomized, parallel group, non-inferiority clinical trial. Results: It was performed in 28 patients (56 eyes) who were randomized into 2 parallel groups (28 eyes per group), the Latanoprost group and the Latanoprostene bunod (LBN) group. In the LBN group, the mean intraocular pressure before treatment was 25.3 ± 6.6 mmHg and the mean intraocular pressure after 1 month of treatment was 16.5 ± 4.9 mmHg (p=0.00). In the Latanoprost group, the mean intraocular pressure before treatment was 23.6 ± 3.6 mmHg and the mean intraocular pressure after 1 month of treatment with 0.005% Latanoprost was 15.3 ± 2.4 mmHg (p=0.00). However, when comparing the IOPs to the 1-month treatment with Latanoprostene bunod 0.024% and Latanoprost 0.005%, it is observed, through ANOVA, that the difference in intraocular pressure reduction between these two drugs is not significant (p= 0.238). Conclusion: Topical prostaglandins, with their potent ocular hypotensive effect (resulting from increased uveoscleral outflow), are an important treatment option for glaucoma. The IOP reduction is as expected with both drugs, however, there are no significant differences between the two. In the LBN group, more drug-related ocular adverse effects were found after 1 month of use.
Keywords: Latanoprost; Latanoprostene bunod; Prostaglandin analogues; Intraocular pressure; Glaucoma